Scientific Morality in the Use of Technology as a Study of the Philosophy of Science on Ethics in the Digital Era - Andi Dewi Riang Tati Dewi; Syamsu A Kamaruddin; Abdullah Sinring; Bahri Bahri (J-CEKI : Jurnal Cendekia Ilmiah, 2025)
The aim of this research is to study scientific morality in the use of technology in the digital era from the perspective of philosophy of science. In the philosophy of science, scientific morality seeks to ensure that technological and scientific developments are driven by ethical and logical considerations. Based on moral values, the use of scientific knowledge not only produces technical progress, but is also socially responsible, making better technology more beneficial to society. This research uses a qualitative approach with a literature study method. The main data source in this research is literature which includes books on the philosophy of science, scientific journals on digital ethics, articles related to scientific morality, as well as previous reports and research on technology in the digital era. Data collection was carried out through literature study, with data analysis using content analysis techniques. Artificial intelligence offers opportunities for progress, but also moral challenges, so developers, policymakers, and society need to collaborate to develop an ethical framework that ensures fair use of the technology and benefits society.